Impact of incubation method on the release of growth factors in non-Ca2+-activated PRP, Ca2+-activated PRP, PRF and A-PRF. Issue 2 (February 2019) - Steller, Daniel; Herbst, Nele; Pries, Ralph; Juhl, David; Hakim, Samer G.
Abstract: The aim of this study was to investigate the influence of different incubation methods on the growth factor content of lysates of platelet-rich fibrin (PRF), advanced-platelet-rich fibrin (A-PRF) and platelet-rich plasma (PRP) products. A comparison of related studies suggests that the method of sample preparation has a significant influence on growth factor content. There are few reports on the comparison of non-Ca 2+ -activated PRP, Ca 2+ -activated PRP, A-PRF, and PRF, along with a lack of information on the release of PDGF-BB, TGF-β1, and VEGF among the different incubation methods. The lysate preparation was made of non-Ca 2+ -activated PRP, Ca 2+ -activated PRP, PRF, and A-PRF, using a room-temperature, 37 °C, or freeze–thaw–freeze incubation method. Afterwards the VEGF, PDGF-BB, and TGF-β1 content was investigated by running ELISA tests. Growth factor levels were significantly increased in the non-Ca 2+ -activated PRP with freeze–thaw–freeze incubation, and in the PRF preparation there was a significant disadvantage to using room temperature incubation for releasing growth factors. In conclusion, the freeze–thaw–freeze method is sufficient for releasing growth factors, and calcium activation is not necessary. Finally, the study demonstrates the possibility of preparing PRP products from platelet concentrates, so that preoperative blood sampling might not be required.